Mesenchymal stem cells for inducing tolerance in organ transplantation - Guo, Kequan; Ikehara, Susumu; Meng, Xu (Frontiers in Cell and Developmental Biology, 2014)
Organ transplantation is useful for treating the end stage of organ failure. The induction of tolerance to the transplanted organ is essential for its long-term survival. Immunologic tolerance can be induced by immunosuppressive agents and mixed chimerism. Mixed chimerism is a state in which both recipient-and donor-derived blood cells remain in the hematopoietic system after allogeneic hematopoietic stem cells have been transplanted. Mesenchymal stem cells (MSCs), and immune cells such as dendritic cells and T-reg cells play an important role in the induction of tolerance. MSCs secrete cytokines, which modulate the immune response. In particular, they upregulate T-reg cell function and thereby induce tolerance. Intra-bone marrow-bone marrow transplantation recruits both donor-derived HSCs and MSCs, inducing persistent donor-specific tolerance without the use of immunosuppressants. In this review, we summarize the use of MSCs to induce tolerance in organ transplantation.